Effectiveness of Gravity and Manual Stress Radiographs and the Use of Lateral Talar Displacement in Determining Ankle Stability of Supination-External Rotation Type Ankle Fractures. Issue 12 (December 2021) - Ali, Raheel A.; Mitchell, Wes; Bora, Varun G.; Dawson, John R.; Atassi, Omar H.; Perkins, Christopher H.
Abstract : Objectives: (1) To evaluate adequacy and reproducibility of the gravity and manual stress imaging in the diagnosis of unstable ankle fractures and (2) to evaluate the diagnostic utility of lateral talar displacement ratio (LTDR) derived in relation to the talar body width on ankle stress imaging. Design: Retrospective cohort study. Setting: Level 1 Trauma Center. Patients: One hundred seventy consecutive patients who presented with supination-external rotation 2 ankle fractures (OTA/AO 44-B2.1) requiring dynamic stress testing. Intervention: Dynamic stress imaging to determine ankle stability. Main Outcome Measure: Ankle instability and subsequent need for surgical fixation as determined by dynamic stress imaging. Results: No statistical significant difference was found between the adequacy of gravity stress radiographs and manual stress images in regards to surgical decision-making ( P = 0.595). Using manual and gravity stress images, receiver operating characteristic curves were generated for medial clear space (MCS) (area under the curve = 0.793, 0.901) and LTDR (0.849, 0.850), corresponding to thresholds of 10.5% and 10.2% for manual and gravity, respectively. Seventy-three of 105 patients (69.5%) with MCS > 5 mm and 62 of 75 patients (82.7%) with LTDR > 10% were offered surgical intervention. Sixty-two of the 77 patients (80.5%) offered surgery had both MCS > 5 mm and LTDR > 10%. Conclusion: This study shows that manual stress radiographs are just as effective as gravity stress radiographs in making an assessment of ankle fracture stability as there was no difference in diagnostic value between gravity and manual stress imaging in regards to surgical decision-making. Use of additional radiographic measurements such as the LTDR can provide additional information in determining stability when MCS is within a clinical gray area. Level of Evidence: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.